Optimal Utilitarian Taxation and Horizontal Equity - Henrik Jordahl; Luca Micheletto (Uppsala University, Department of Economics, 2002)
We impose a horizontal equity restriction on the problem of finding the optimal utilitarian tax mix. The horizontal equity constraint requires that individuals with the same ability have to pay the same amount of taxes regardless of their preferences for leisure. Contrary to normal findings, we find that a good that is complementary to leisure need not be discouraged by the tax system, and that a good that normally should be discouraged by the tax system need not be taxed at a positive rate even if the economy is composed of only two private commodities plus leisure. Similarly, the marginal effective tax rate need not be equal to zero at the top when the tax mix obeys the horizontal equity constraint.
urn:nbn:se:uu:diva-4450
Keywords: D63; H21; H24; 330; Horizontal equity; optimal taxation; heterogeneous preferences; utilitarianism; Optimale Besteuerung; Verteilungsgerechtigkeit; Utilitarismus; Theorie